Development of Blended Learning Model Using Gamification in Computers Technology and Application for Learning Management Course to Enhance Creativity for Education Students - Thitipetchakul, Chanin; Samutpaojinda, Prapawon (Ratchaphruek Journal, 2021)
This research was a study of the blended learning model using Gammification. The purposes were to: 1) Develop the blended learning model using Gamification; 2) Study the result of using the blended learning model using Gamification; and 3) Study students’ satisfaction towards the blended learning model using Gamification. The sample of this study were the 5 experts and the 30 undergraduate students of Suan Dusit University that studying in the course on computer technology and application for learning management obtained from cluster random sampling. The research tools were: 1) Computer program with gamed-based, 2) learning achievement test, 3) rubric assessment of creativity, and 4) satisfaction questionnaire. Statistics were analyzed by means, standard deviation, and dependent samples t-test. The research results revealed that: 1. The developed blended learning management model using Gamification comprised 3 components: Blended learning management system, Gamification learning environment, and learning process; 2. The achievement scores of students were higher than before and were statistically significant at .05 level; 3. The creativity of the students was at a good level; and 4. Students satisfaction’s scores with the blended learning based on Gamification were at the highest level.